3D printed microfluidic in-vitro model to study atherosclerosis - Phua, Zhai Juan (2017)
Microfluidics is the perfusion of precise amounts of fluids across channels in the micrometer-scale. It has been incorporated into many research areas such as molecular biology, DNA microfluidics and for creating biomimetic models. These biomimetic models could potentially decrease the lengthy duration of the drug discovery process by skipping the preclinical research step. In addition, the ability to incorporate a patient’s cells into the microfluidic devices could improve point of care by testing for patient-specific drug effectiveness or allergies. The focus of this study was to determine the suitability of using additive manufacturing (AM) in the preparation of microfluidic devices, and thereafter altering these devices to obtain representative models of the human artery. The 3D printer used in this study utilises the stereolithography (SLA)technology, a resin-based AM technology that produces printed parts with superior surface finishes compared to other solid- or powder-based AM technologies [1]. The surface finish of the microfluidic molds plays a crucial role in the subsequent steps of device preparation and for experimentation. After the mold design was finalised for ease of removal, and the part dimensions calibrated to account for print tolerances, the study was extended into three subprojects, namely: 1) Secondary Fabrication of circular PDMS microfluidic channels Rectangular PDMS microfluidic channels produced from 3D printed molds were modified by a process inspired by L. Fiddes [2]. Uncured PDMS was introduced, followed by passing of an airstream to create a through channel, and then heated to form the circular lumen. Channels were the cross-sectioned and imaged to determine the effects of i) air pressure and ii) perfusion time on lumen diameter. 2) Perfusion of circular PDMS channels seeded with endothelial cells in different flow conditions, to investigate varying cell expressions Circular PDMS microfluidic channels were seeded with endothelial cells along the lumen circumference. The microfluidic devices were then perfused in the following conditions: i) 10dyncm^-2 for 24 hrs; ii) 10dyncm^-2 for 48 hrs; and iii) static (no flow). Cells were then fixed and stained with fluorescent markers to be imaged by confocal microscopy. Parameters of interest were the effect of perfusion on: i) cell alignment; ii) cell morphology; and iii) cell-to-cell adhesion. 3) Secondary Fabrication of collagen microfluidic channels to support coculture As the method in sub-project 1 was unsuitable for hydrogel material, the Viscous Finger Patterning method introduced by L. Bischel [3] was used instead to modify channel geometry. A circular lumen within a collagen matrix would be able to support the culture of smooth muscle cells within the collagen, and the culture of endothelial cells along the lumen circumference, better replicating in-vivo conditions for atherosclerosis study.